2014
DOI: 10.1016/j.neuron.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Delta Opioid Receptors Presynaptically Regulate Cutaneous Mechanosensory Neuron Input to the Spinal Cord Dorsal Horn

Abstract: The original version of this article omitted two citations. These papers provide a seminal description of retinal waves (Meister et al., 1991) and their effects on retinogeniculate patterning (Penn et al., 1998). These citations have been added, and the article has now been corrected online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(104 citation statements)
references
References 0 publications
11
93
0
Order By: Relevance
“…Peptidergic C-fibers are essential to acute heat pain as well as injury-induced heat hyperalgesia (Cavanaugh et al, 2009) and have been shown to project to laminae I and II outer of the spinal cord ) where robust NOP Receptor Biology and Function immunoreactivity of NOP-eGFP is also observed. A smaller proportion of small unmyelinated (NF200-) NOP-eGFP+ DRG neurons bind IB4, indicating that NOP receptors are also present in the non-peptidergic DRG neurons, which are involved in mechanical pain Cavanaugh et al, 2009;Scherrer et al, 2009;Vrontou et al, 2013;Bardoni et al, 2014). These studies suggest that NOP receptors might regulate the function of two classes of C nociceptors that respond to both heat and mechanical pain.…”
Section: B Location Of Nociceptin Opioid Peptide Receptorsmentioning
confidence: 89%
“…Peptidergic C-fibers are essential to acute heat pain as well as injury-induced heat hyperalgesia (Cavanaugh et al, 2009) and have been shown to project to laminae I and II outer of the spinal cord ) where robust NOP Receptor Biology and Function immunoreactivity of NOP-eGFP is also observed. A smaller proportion of small unmyelinated (NF200-) NOP-eGFP+ DRG neurons bind IB4, indicating that NOP receptors are also present in the non-peptidergic DRG neurons, which are involved in mechanical pain Cavanaugh et al, 2009;Scherrer et al, 2009;Vrontou et al, 2013;Bardoni et al, 2014). These studies suggest that NOP receptors might regulate the function of two classes of C nociceptors that respond to both heat and mechanical pain.…”
Section: B Location Of Nociceptin Opioid Peptide Receptorsmentioning
confidence: 89%
“…Previous attempts at targeting ␦R to manage pain have mainly focused on developing better ␦R agonists (Scherrer et al, 2009;Gavériaux-Ruff and Kieffer, 2011;Bardoni et al, 2014). However, these efforts have largely been unsuccessful, as available agonists show poor in vivo efficacy, necessitating the use of high doses that cause adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…␦R expressed in nociceptive neurons can reduce cAMP and inhibit Ca 2ϩ channels to inhibit neuronal activity (Jutkiewicz et al, 2006;Cahill et al, 2007;Pradhan et al, 2011;Bardoni et al, 2014). ␦R agonists can cause antinociception in some conditions, and they show reduced abuse liability compared with current opioids that target the opioid receptor (R) ( Vanderah, 2010;Gendron et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…showed that DOR presynaptically regulate mechanical inputs from sensory neurons to spinal cord (74). Thus, it is conceivable that DORs expressed on mechanosensitive fibers mediate the pain-suppressive effects of enkephalins released from the RVMpre neurons, even when RVM release of GABA is blocked.…”
Section: Discussionmentioning
confidence: 99%